2005
DOI: 10.2527/2005.832449x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proportion of pigs removed from a group and subsequent floor space on growth performance of finishing pigs1

Abstract: The effects of the proportion of pigs removed from an established group and subsequent floor space on growth performance during the final 19 d of the finishing period were evaluated using 28 pens of mixed-sex crossbred pigs (mean initial BW = 113.4 +/- 0.57 kg; n = 1,456; approximately 52 pigs per pen). A randomized block design was used with four pig-removal treatments: 1) 0% of pigs removed [Control], 2) approximately 25% of pigs removed, 3) approximately 50% of pigs removed, and 4) approximately 50% of pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 6 publications
5
32
0
Order By: Relevance
“…Growth performance results from the current study agree with previous research examining the impact of removals on finishing pig growth performance (Woodworth et al, 2000;DeDecker et al, 2005;Jacela et al, 2009) in the sense that removing heavy-weight pen mates from a pen results in the remaining pigs having increased ADG and ADFI compared to pigs in intact pens. Interestingly, Bates and Newcomb (1997) and Woodworth et al (2000) observed no impact of pig removal on the G:F of those animals remaining.…”
Section: Growth Performancesupporting
confidence: 82%
See 3 more Smart Citations
“…Growth performance results from the current study agree with previous research examining the impact of removals on finishing pig growth performance (Woodworth et al, 2000;DeDecker et al, 2005;Jacela et al, 2009) in the sense that removing heavy-weight pen mates from a pen results in the remaining pigs having increased ADG and ADFI compared to pigs in intact pens. Interestingly, Bates and Newcomb (1997) and Woodworth et al (2000) observed no impact of pig removal on the G:F of those animals remaining.…”
Section: Growth Performancesupporting
confidence: 82%
“…After the removals occurred, BW CV numerically decreased for pigs remaining in pens on the 2:2:2 and 2:4 removal strategies, but only the 2:2:2 removal strategy CV was significantly less (P = 0.004) than that of pigs in pens initially provided 0.91 m 2 of floor space. On d 95 prior to removals, the 2:2:2 removal strategy pigs had less (P < DeDecker et al (2005) concluded that BW variation within pen was reduced with the removal of the heaviest pigs, but the rate of reduction was dependent on the number of pigs removed and the time of measure after removals. Previous work by DeDecker et al (2002) concluded that removing the heaviest 25% of the pen reduced within-pen BW variation, but by 21 d postremoval the BW variation was similar regardless of removal strategy.…”
Section: Within-pen Bw Variationmentioning
confidence: 98%
See 2 more Smart Citations
“…The lower ambient temperature in the OUT system may explain the higher feed intake of these animals and, consequently, their faster growth rate, in accordance with the well-established effects of ambient temperature on the growth performance of ad libitum fed pigs (Le Dividich et al, 1998). Another explanation is the larger floor space in the OUT system compared with the CON system that provides an easier access to the feeder, in particular at the end of the fattening period, thus giving rise to higher growth rates (Hamilton et al, 2003;DeDecker et al, 2005). Higher feed intake and growth rate of pigs finished in enriched (straw, 3.5 m 2 /pig) compared with barren (slatted floor, 0.76 m 2 /pig) environments have been reported by Beattie et al (2000), in agreement with the present results.…”
Section: Discussionmentioning
confidence: 99%